PERANCANGAN PROMOSI DISTRO CORAL GIRLS PEKANBARU MELALUI MEDIA WEBSITE - DENI PRATAMA, Drs. Syafwandi, M.Sn, Drs. Ady Rosa,M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Distro Coral Girls is one of the distributions that are new in town week. These distributions have been established since 2003 At the beginning of this distribution named SK8 and in 2006 changed to Coral who the target audience is men and since 2011 distributions Coral changed its name to Coral Girls who the target audience is also changed into a woman. Address distributions Coral Girls in Jln. Kaharudin Nasution No. 142 and 143, Marpoyan, Pekanbaru. After changing the name and the target aundience, Coral Girls distributions have not been doing a special promotion. Promotion is done only by fuel and by word of mouth.From these two distributions made Coral Girls design promotion through media websites. The website is a place or location in the Internet network created by companies, organizations or individuals and can be visited by anyone. Website chosen as the main medium for technology and information today is so readily available.Design method used is the SWOT analysis. The advantages of this website is the media have access to a wide range of media that never cease operations, the visual display is interactive and engaging. The weakness of this medium, to be able to access the website should have an internet connection and a device and a slow loading process.The era of technology and information is now easily encountered and used, so it can be used for the promotion of distributions Coral Girls in a web form. Supported by other media ie business cards, pins, key chains, shopping bags, posters, mugs, stickers, bookmarks, handbooks and T shirtsKata Kunci : Desain, Website, Distro Coral Girls